Police and community responses to youth gangs - White, R. D. (Robert Douglas), 1956-; Australian Institute of Criminology (Canberra : Australian Institute of Criminology, 2004)
Although there are no national data on youth gangs in Australia there is a perception that youth gangs are an emerging problem. This paper draws largely on overseas attempts to deal with gang related activity and the extent to which they have been successful. The most successful interventions have some combination of coercive and developmental measures. A key issue for both policy makers and practitioners is the weight given to particular measures within the context of an overall strategy. While for tactical purposes, coercive force may occasionally be necessary, positive approaches to gang issues also require developmental strategies and active community involvement.
"March 2004".
Caption title.
Includes bibliographical references (p. 6).
Also available in an electronic version via the Internet. Address as of 08/04/2004: http://www.aic.gov.au/publications/tandi2/tandi274.pdf
System requirements: Adobe Acrobat Reader required to view/print pdf files.
Keywords: Suburban gangs -- Australia; Gang prevention -- Australia; Gang prevention; Gangs -- Australia